2021
DOI: 10.1542/peds.2021-052273
|View full text |Cite
|
Sign up to set email alerts
|

Deaths in Children and Adolescents Associated With COVID-19 and MIS-C in the United States

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 39 publications
2
66
1
4
Order By: Relevance
“… 7 Even in the United States, deaths are more frequent among the most vulnerable populations. 28 In Brazil, it is no different. In this study, mortality was 2-3-fold higher than those reported in the United States and Europe.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Even in the United States, deaths are more frequent among the most vulnerable populations. 28 In Brazil, it is no different. In this study, mortality was 2-3-fold higher than those reported in the United States and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, several authors reported case series of deceased pediatric patients. McCormick et al 46 reported 112 deaths, with a median age of 17 years (range 0-21 years): 63% were male, and 86% of patients presented with at least one of the following conditions: obesity (42%), asthma (29%), and developmental disorders (22%). Similarly, Bixler et al 47 reported 121 deaths in patients under 21 years old: only 30 (25%) were patients otherwise healthy, whereas 91 (75%) patients had at least one comorbidity, and 54 (45%) had two or more comorbidities: asthma (28%), obesity (27%), neurologic and developmental conditions (22%), cardiovascular diseases (18%), cancer or immune system disorder (14%) and diabetes mellitus (9.1%).…”
Section: Sars-cov-2 Infection and Covid-19 In Children Andmentioning
confidence: 99%
“…Children with underlying diseases show higher risk for severe manifestations of COVID-19. 9 10 11 12 13 19 21 Recent studies in children have identified type 1 diabetes, obesity, cardiac and circulatory congenital anomalies, epilepsy and convulsions, neurodevelopmental disorders, type 2 diabetes, other chronic complex diseases and prematurity in children < 2 years as high risk of need for hospitalization or severe COVID-19. 11 12 13 Among various risk factors, diabetes mellitus is identified as a high risk for hospitalization and severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 7 8 9 Among age groups in children, admission rates are highest in 0–4 years of age followed by 12–17 years and lowest among children 5–11 years of age, 8 whereas mortality has been reported in younger (0–2 years) or older age groups (12–19 years). 10 …”
Section: Introductionmentioning
confidence: 99%